Signaling and Screening of Workers' Motivation - Josse Delfgaauw; Robert A.J. Dur (Tinbergen Institute, 2002)
This paper develops a model in which workers are heterogeneous in their intrinsic motivation to work at a firm. We characterise optimal incentive schemes and examine how the firm can attract and select highly motivated workers to fill a vacancy when workers' motivation is private information. While posting a higher wage increases the probability of filling the vacancy, it decreases the expected average quality of job applicants because less motivated workers are induced to apply. The optimal wage scheme entails a trade-off between the probability of filling the vacancy, the rents left to the worker, and the expected worker's motivation.
Keywords: D82; J31; J42; 330; signaling and screening models; intrinsic motivation; monetary incentive schemes; minimum wages.; Leistungsanreiz; Anreizvertrag; Signalling; Mindestlohn; Leistungsmotivation; Verhandlungstheorie; Theorie